1836. Frequency and Antimicrobial Susceptibility of Gram-negative Bacteria Isolated from Patients with Bloodstream Infections in United States (US) Medical Centers (2020-2021). (15th December 2022) - Sader, Helio S; Mendes, Rodrigo E; Carvalhaes, Cecilia G; Huband, Michael D; Shortridge, Dee; Castanheira, Mariana
Abstract: Background: Antimicrobial resistance among Gram-negative bacteria (GNB) is a major problem in US hospitals. The development of various β-lactamase inhibitor combinations (BLICs) markedly increased the armamentarium to treat infections caused by GNB in recent years. We evaluated the frequency and antimicrobial susceptibility of GNB causing bloodstream infection (BSI). Methods: 5, 796 organisms were consecutively collected (1/patient) from patients with BSI in 31 US medical centers in 2020-2021. The collection included 2, 893 (49.9%) GNB, which were susceptibility tested against ceftazidime-avibactam (CAZ-AVI), ceftolozane-tazobactam (C-T), meropenem-vaborbactam (MEM-VAB), imipenem-relebactam (IMI-REL), and many comparators by CLSI broth microdilution method. Enterobacterales (ENT) isolates with an ESBL phenotype were screened for β-lactamase genes by whole genome sequencing. Results: The most common GNBs were E. coli (41.9%), K. pneumoniae (16.1%), P. aeruginosa (10.2%), and E. cloacae (6.8%). Ceftriaxone susceptibility rates were 80.1%, 82.9%, and 74.0% for E. coli, K. pneumoniae, and E. cloacae, respectively. CAZ-AVI and MEM-VAB showed almost complete activity (≥ 99.7%) against ENT, whereas IMI-REL exhibited limited activity against P. mirabilis and indole-positive Proteeae isolates and C-T showed limited activity against E. cloacae, ESBL-phenotype, and multidrug-resistant (MDR) isolates (Table). CAZ-AVI, MEM-VAB, and IMI-REL were active against 84.2%, 57.9%, and 52.6% of carbapenem-resistant ENT (CRE) isolates, respectively. PSA susceptibility to PIP-TAZ, MEM, and CAZ were 86.1%, 88.5%, and 88.5%, respectively. CAZ-AVI (97.6% susceptible [S]), C-T (97.6%S), IMI-REL (99.0%S), and tobramycin (TOB; 98.3%S) were the most active agents against PSA and retained good activity against piperacillin-tazobactam (PIP-TAZ) nonsusceptible (NS), MEM-NS, and multidrug-resistant (MDR) isolates. Conclusion: CAZ-AVI and MEM-VAB were the most active agents against ENT and CAZ-AVI; C-T and IMI-REL were the most active BLICs against PSA. The new BLICs represent valuable treatment options for infections caused by MDR GBNs. CAZ-AVI exhibited a more balanced spectrum against ENT and PSA when compared to other BLICs. Disclosures: Helio S. Sader, MD, PhD, AbbVie: Grant/Research Support|Cidara: Grant/Research Support|Melinta: Grant/Research Support|Nabriva Therapeutics: Grant/Research Support|Pfizer: Grant/Research Support Rodrigo E. Mendes, PhD, AbbVie: Grant/Research Support|Cidara: Grant/Research Support|GSK: Grant/Research Support|Melinta: Grant/Research Support|Nabriva Therapeutics: Grant/Research Support|Office for Assistant Secretary of Defense for Health Affairs: Grant/Research Support|Pfizer: Grant/Research Support|Shionogi: Grant/Research Support|Spero Therapeutics: Grant/Research Support Cecilia G. Carvalhaes, MD, PhD, AbbVie: Grant/Research Support|Cidara: Grant/Research Support|Melinta: Grant/Research Support|Pfizer: Grant/Research Support Michael D. Huband, BS, AbbVie: Grant/Research Support|Melinta: Grant/Research Support Dee Shortridge, PhD, AbbVie: Grant/Research Support|JMI Laboratory: Employee|Melinta: Grant/Research Support|Menarini: Grant/Research Support|Shionogi: Grant/Research Support Mariana Castanheira, PhD, AbbVie: Grant/Research Support|Cidara: Grant/Research Support|GSK: Grant/Research Support|Melinta: Grant/Research Support|Pfizer: Grant/Research Support|Shionogi: Grant/Research Support.